Properties of hot electrons in the Jovian inner magnetosphere deduced from extended observations of the Io Plasma Torus. Issue 22 (23rd November 2016) - Yoshikawa, Ichiro; Yoshioka, Kazuo; Murakami, Go; Suzuki, Fumiharu; Hikida, Reina; Yamazaki, Atsushi; Kimura, Tomoki; Tsuchiya, Fuminori; Kagitani, Masato; Sakanoi, Takeshi; Uemizu, Kazunori; Tao, Chihiro; et al.
Abstract: One of the focal points of interest in Jovian magnetospheric physics is the transport of energy and particles into the inner region. While an explosive energy release event in the midmagnetosphere is manifested as an aurora transient, its connection to the inner part has not been investigated due to sparsity of observations. Here we take the advantage of long‐term and quasi‐continuous simultaneous monitoring of the polar aurora and the Io Plasma Torus (IPT) located in the inner magnetosphere by Extreme Ultraviolet Spectroscope for Exospheric Dynamics/Hisaki. Studies on temporal characteristics over hours enable us to see slow (~10 h) coupling between the middle and inner magnetosphere as well as to quantify the temperature of hot electrons in the IPT. We derive parameters that characterize the strong particle acceleration process. Key Points: Continuous monitoring of the Io Plasma Torus (IPT) and Jovian aurora by EXCEED/Hisaki reveals middle‐inner magnetospheric coupling Inward transport time scale of hot electrons between the two regions is ~10 h The light curve analysis of the IPT emission reveals that characteristic energy of hot electrons inside IPT is approximately a few hundreds of eV